The effect of Ease of Use, Seller Reputation, and Perceived Usefulness On Brand Loyalty with Satisfaction as a Mediating Variable - Dilan Raihan; Soepatini (SAFE-Network, 2023)
This study is to determine the effect of customer satisfaction in building brand loyalty through customer satisfaction, ease of use, seller reputation, and perceived usefulness. The population of this study, which employs quantitative research techniques, consists of Surakrarta-based customers of online marketplaces. Purpose Sampling was the method of sampling employed in this investigation. They employed 127 respondents. The information used in this study came through the distribution of questionnaires. Partial Least Square (PLS) data analysis using SMARTPLS software is the method used in this study. According to the findings of this study, Brand Loyalty is not positively and significantly impacted by Seller Reputation, Perceived Usefulness, or Ease of Use. A favorable and considerable impact on satisfaction is provided by the ease of use, seller reputation, and perceived usefulness. Brand Loyalty is positively and significantly impacted by satisfaction. Ease of Use, Seller Reputation, and Perceived Usefulness cannot be mediated by satisfaction in determining brand loyalty.This research contributes to increasing knowledge in the sector of selling used products through online platforms, because one of the challenges faced by the MSME industry is the use of technology in its business processes. The use of technology can facilitate business activities such as, means of promotion and facilitate transactions because this convenience is used by umkm industry business actors and consumers in the use of technology.